USP36-Mediated Deubiquitination of DOCK4 Contributes to the Diabetic Renal Tubular Epithelial Cell Injury via Wnt/β-Catenin Signaling Pathway - Zhu, Suwei; Hou, Shaoshuai; Lu, Yao; Sheng, Wei; Cui, Zhengguo; Dong, Tianyi; Feng, Hong; Wan, Qiang (Frontiers in Cell and Developmental Biology, 2021)
Diabetic kidney disease (DKD) has become the leading cause of end-stage renal diseases, but the efficacy of current treatment remains unsatisfactory. The pathogenesis of DKD needs a more in-depth research. Ubiquitin specific proteases 36 (USP36), a member of deubiquitinating enzymes family, has aroused wide concerns for its role in deubiquitinating and stabilizing target proteins. Nevertheless, the role of USP36 in diabetes has never been reported yet. Herein, we identified an increased expression of USP36 both in vitro and in vivo in diabetic renal tubular epithelial cells (TECs), and its overexpression is related to the enhanced epithelial-to-mesenchymal transition (EMT). Further investigation into the mechanisms proved that USP36 could directly bind to and mediate the deubiquitination of dedicator of cytokinesis 4 (DOCK4), a guanine nucleotide exchange factor (GEF) that could activate Wnt/β-catenin signaling pathway and induce EMT. Our study revealed a new mechanism that USP36 participates in the pathogenesis of DKD, and provided potential intervening targets accordingly.